The interplay between species and locations shapes vector fleas microbial communities in plague foci: pathogens rather than symbionts? - Seidi, Shahin; Raz, Abbasali; Maleki-Ravasan, Naseh; Forouzan, Esmaeil; Karimian, Fateh; Sebbane, Florent; Sohrabi, Aria; Esmaeili, Saber; Mostafavi, Ehsan (Frontiers in Cellular and Infection Microbiology, 2025)
Besides causing allergies from their bites, fleas transmit the most notorious zoonotic pathogen, Yersinia pestis. They also harbor commensal bacteria in their guts. Here, the microbial communities of fleas were characterized using 16S rRNA Next-Generation Sequencing to understand microbial interactions and functions in areas with historical plague-outbreaks in Iran with the ultimate idea of ​​managing flea-borne diseases. Meriones persicus, Xenopsylla buxtoni and Bartonella spp. were identified as the dominant host, vector and bacterium, respectively. Six bacteria Bartonella, Sphingomonas, Wolbachia, Cardinium, Rickettsia and Ralstonia were identified as the most abundant genera in the microbiome of five flea species. More detailed surveys revealed substantial intrageneric variations (e.g. nine phylotypes for Bartonella) and the diverse nature (from biofilm-forming human pathogens to insect reproductive manipulators, and environmental microbes) for the bacteria studied. The fleas microbiome is largely affected by species and to a lesser extent by location, and circulates by both horizontal and vertical transmissions. The prevalence of Bartonella spp. infection in fleas highlights the potential to explore One Health approaches, particularly in addressing travel-related and zoonotic disease risks. Environmental drivers—such as climate change, habitat alteration, and host dynamics—shape flea microbiomes and influence disease risk, while concerns about antimicrobial resistance further complicate control efforts. Our findings advocate for coordinated strategies that combine public health education, ecological monitoring, and global collaboration to sustainably manage flea-borne diseases.